Analisis Nilai Estetika dan Makna Visual Karya Pemenang Lomba Desain Batik Kota Tangerang Selatan 2023 - Fariz Al Hazmi (JURNAL RUPA, 2024)
The process of designing motifs is one of the stages in making batik work before processing. This process requires creativity and knowledge in making something into a motif. In the batik design competition held by the City of South Tangerang in 2023, one work was won with the title "Triasih Nawasena". The aim of this research is to examine aesthetics and describe meaning through a semiotic approach. The research method uses descriptive qualitative with data collection through observation, semi-structured interviews and literature study. The interview was conducted with Septi Rahmawati as the winner of the competition and owner of the work. The research results show that the "Triasih Nawasena" batik design has three motif elements, namely the main motif, complementary motifs and filling motifs or isen-isen. These motifs complement each other with the main motif being made larger but the number is not too dominant compared to the complementary motifs. Meanwhile, isen-isen is used to create texture in certain motifs. So that the overall design has design elements such as points, lines, shapes, textures, space and color in each motif and becomes one unit. All of the motifs on this batik have meanings that represent typical objects in South Tangerang City.